Workshop Online Otomasi Distributed Control System Berbasis Internet-Of-Things di SMK PALAPA Mojokerto - Mimin Fatchiyatur Rohmah; Rokhmad Eko Cahyono; Yanuarini Nur Sukmaningtyas; Luki Ardiantoro (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
Automatic control technology based on the Internet of Things (IoT) is growing rapidly in the scope of the production process. This technology is able to increase quantity and improve quality so that production result have high competitiveness for customer satisfaction. DCS or Distributed Control System is one of the most popular process control technology implementations today.  The rapid development of DCS is still not balanced with the knowledge of vocational students about the practical knowledge gained at schools. The purpose of this activity is to provide practical knowledge and understanding to students regarding DCS technology, network topology and IoT technology which also equipped with several examples of production process videos in factories, to narrow the gap between knowledge taught in schools and process technology in factories. In addition to the DCS core material, students are also given additional material on artificial intelligence technology, machine learning and data mining which are also related to the quality of production results. In accordance with the Covid 19 health protocol, this community service workshop was held online with webinar using the Google Meet application. As a result of this activity, the students of SMK Palapa Mojokerto gain broader insight about process technology in factories to increase competence in competing in the world of work.Keywords: Covid-19, DCS, Internet Of Things, Artifial Intelligence, Webinar, Workshop ABSTRAKTeknologi pengendalian otomatis berbasis Internet of Things (IoT) berkembang pesat pada lingkup proses produksi. Teknologi ini mampu meningkatkan kuantitas dan memperbaiki kualitas sehingga hasil produksi memiliki daya saing tinggi untuk kepuasan pelanggan. DCS atau Distributed Control System merupakan salah satu dari implementas teknologi pengendalian proses yang sangat terkenal pada masa ini. Perkembangan pesat DCS masih belum seimbang dengan pengetahuan siswa SMK mengenai ilmu praktis yang didapat di sekolah. Tujuan kegiatan ini adalah memberi bekal pengetahuan praktis dan pemahaman pada siswa mengenai teknologi DCS, topologi jaringan dan teknologi IoT yang dilengkapi juga dengan beberapa contoh video proses produksi di pabrik, untuk mempersempit adanya gap antara pengetahuan yang dijarkan di sekolah dengan teknologi proses di pabrik.  Selain materi inti DCS, siswa juga diberikan materi tambahan tentang teknologi kecerdasan buatan, machine learning dan data mining yang berhubungan juga dengan kualitas hasil produksi.  Sesuai protokol kesehatan Covid-19, Workshop pengabdian masyarakat ini dilaksanakan secara daring dengan webinar menggunakan aplikasi google meet. Hasil dari kegiatan ini siswa SMK Palapa Mojokerto mendapatkan wawasan lebih luas mengenai teknologi proses di pabrik untuk  meningkatkan kompetensi dalam bersaing di dunia kerja.Kata Kunci: Covid-19, DCS, Internet Of Things, Kecerdasan Buatan, Webinar, Workshop